La Lente Evolution Du Système Fiscal Marocain : Les Faits Et Les Enseignements - Barka, M. Hafid; Hassainate, M. Mohammed Saber (European Scientific Journal, ESJ, 2018)
The present work aims to analyze the evolution of the Moroccan tax system from the independence to the implementation of the tax reform of the 1980s in order to draw the lessons and to be able to decide on its future evolutions. Indeed, fiscal developments and "reforms" succeeded one another since the independence in 1956, with no significant evolution in the Moroccan tax system inherited from the French protectorate. Yet this system was characterized by imbalances; inconsistencies and inequities. A profound tax reform has become inevitable. After an undue delay; The Government has proceeded from 1984 to the reform of the effective tax system with a view to its modernization and simplification. This reform has resulted, in fact, in the passage of a heavy and complex schedular or analytical system, characterized by blatant inequalities, imbalances and inconsistencies to a modern and synthetic taxation system. At the end of this reform; three major synthetic taxes were set up: T.V.A, I.S and I.R. The reform also concerned the taxation of local authorities. With the implementation of the tax reform since 1984, the Moroccan tax system has certainly made progress but limitations related in particular to the architecture of the system and its structure and new synthetic taxes persist. Future research will focus on assessing the tax reforms and adjustments of the years 2000 and the prospects for reforming the Moroccan tax system.